Draft genome sequence of an enterotoxigenic Escherichia coli strain carrying genes for colonization surface antigen 13 and a heat-labile toxin - Njoroge, Samuel M.; Madé, L.F.; Mentzer, A. von; Kulohoma, B.W.; Kamanu, T.K.; Ouko, T.T.; Kiiru, J.; Ward, M.J.; Thomson, N.R.; Fèvre, Eric M.; Woolhouse, Mark E.J.; Kariuki, S. (American Society for Microbiology, 2022)
Here, we report the draft genome of ESEI_597, an enterotoxigenic Escherichia coli (ETEC) strain harboring genes encoding colonization surface antigen 13 (CS13) and a heat-labile toxin. The ESEI_597 strain was isolated from an 8-month-old child living in Korogocho, Kenya, in 2013.